The Influence of Work Ethic, Work Stress, And Work Environment on Employee Performance at PT. Perkebunan Nusantara IV Regional III Kebun Tandun - Yosef Heskyel Pardosi; Toman Panggabean; Winarto Winarto; Maludin Panjaitan (Fakultas Ekonomi Universitas Simalungun, 2026)
This study aims to determine the extent to which work ethic, work stress, and work environment contribute to improving employee performance at PT. Perkebunan Nusantara IV Regional III Kebun Tandun. This study uses quantitative research. The sample in this study consisted of 88 respondents who are employees at PT. Perkebunan Nusantara IV Regional III Kebun Tandun. Based on the results of the t-test hypothesis, it can be concluded that work ethic partially has a positive and significant effect on employee performance with a calculated t-value of 5.189 > t-table 1.988 and a significance value of 0.001 < 0.05. Work stress partially has a positive and significant effect on employee performance with a calculated t-value of 4. 114 > t table 1.988 and a significance value of 0.001 < 0.05, the work environment partially has a positive and significant effect on employee performance with a t-value of 4.508 > t table 1.988 and a significance value of 0.000 < 0.05. Based on the results of the F hypothesis test, it can be concluded that work ethic, work stress, and work environment simultaneously have a positive and significant effect on employee performance. Based on the results of the coefficient of determination analysis, it can be concluded that the effect of work ethic, work stress, and work environment on employee performance is 92.8%